A compreensão sobre o processo de obtenção do consentimento livre e esclarecido em pesquisa com seres humanos: um estudo com pesquisadores da Faculdade de Odontologia daUniversidade Federal de Minas Gerais - Elza Maria de Araujo Conceicao (2008)
This study involves the presentation of two articles prepared from the research conducted with dentists researchers of the Dentistry School of the Universidade Federal de Minas Gerais (FOUFMG) involved in studies with human beings. The research was made in continuity of the first study conducted by myself, in 2002, that measured the use of the Informed Consent (IC), as a strategy to disseminate good practice of care in the clinics of the FOUFMG. After obtained results, it became necessary to confront the understanding of the professors researchers with theexisting standards of research on human beings, as well as the role of the agencies responsible for implementing these standards in the teaching and research institutions. Because of the complexity of the theme, we chosen to focus on the comprehension of the dentists researchers about obtaining the consent, based upon the principles of bioethics and the IC, which mandatory documents the researchprojects. Ten researchers were randomly selected among those who presented projects analyzed by the Ethics Committees in Research of UFMG - COEP/UFMG in the period of 2000 to 2004. This 10 participants answered questions related to three situations: an invitation to participate in a hypothetical study as a volunteer, to conduct a study as a researcher and to analyze an Informed Consent, selected from the projects examined by the COEP/UFMG, in the period mentioned above. In eachsituation were analyzed: the degree of adherence of the project to the rules and the preservation of the autonomy of the volunteer. The data obtained was discussed in bioethics principles, which constitute the conceptual framework of this study, and the analysis of themes and categories were constructed from the contents of the interviews. From the statement analysis, it was found that the respondents knew much of ethical standards, the responsibility of the researcher and the limits of action of the Ethics Committees in Research. The statements also demonstrated that the professors researchers recognize that they need to increase their reflection about the principles that guide the research in human beings, and avoid the merely administrative compliance of regulatory requirements. They also recognize and require a better involvement of the Ethics Committees in Research in the process ofinstitutionalization of ethics in research.